A new kind of research. Issue 9 (September 2018) - Mercer, Stewart; Gillies, John; Calderwood, Catherine; Smith, Gregor
General practice is entering a period of rapid change and requires research evidence to guide it. The 'gold standard' model of research, based on randomised controlled trials that are expensive, take several years to complete, and even more years to be implemented, is insufficient to inform the rapidly changing primary care landscape. This article will discuss a new kind of research, co-produced by academics, patients, and NHS staff, which offers a more realistic approach to informing policy and service development in a timely manner. We use the example of multimorbidity to discuss the need for such research. Multimorbidity is not the only population challenge that general practice faces, but it is a key one. Given the very limited evidence-base for how best to manage patients with multimorbidity, discussed in more detail below, it is a prime target for a new kind of research.